Tools for the Virtual:: Atmosphere and Bodily Presence of Digital Space - Böck, Ingrid (ARCC Conference Repository, 2019)
Architecture of the digital space is increasingly evolving towards the imaginary, atmospheric, and invisible sphere beyond the reality of built space. The virtual world of digital technologies has changed the practice of the design process by blurring the boundaries between fictitious and real space. Experimental conditions of layering, folding, and programmed randomness of algorithms via the means of combined software enable the visual representation of architectural hybrids. This new reality of the design process is envisioned as renderings, virtual 3d building models, diagrammatic projections, and animated movies. Yet, how can the innovation of the digital turn in the design process effect, shape and interact with our perception and experience of space? Are the digital and the analogue world fundamentally different as their means and techniques may suggest?